Primordial Wormholes and their Traversability Constraints: In the Context of the Presence and Absence of Exotic Matter - Al Dallal, Shawki (European Journal of Applied Sciences, 2026)
Wormholes, though never directly observed, arise as legitimate solutions to the field equations of general relativity. Early work by Patton and Wheeler introduced the concept of quantum foam, wherein the gravitational vacuum at the Planck scale consists of fluctuating microscopic geometries. Among these configurations, submicroscopic wormholes may naturally emerge, particularly in the extreme conditions of the early universe. Governed by the uncertainty principle, such wormholes are expected to be highly transient. However, it has been conjectured that quantum fluctuations could enable their gradual growth, allowing Planck-scale wormholes to expand to microscopic or even macroscopic sizes. During the inflationary epoch, this process might have produced an interconnected network of primordial wormholes. Classically, wormholes are unstable and rapidly collapse into singularities. To render them traversable, Kip Thorne and collaborators proposed the necessity of exotic matter, which counteracts gravitational collapse by violating the null energy condition through negative stress-energy density. While exotic matter is not observed macroscopically, quantum field theory permits negative energy densities and fluxes under strict constraints imposed by quantum inequalities. In this work, we present a comprehensive analysis of various theoretical models proposed to stabilize wormholes, assessing their consistency within the broader framework of quantum gravity and early-universe cosmology. We further investigate the potential role of antimatter and the implications of charge–parity–time (CPT) violation in both flat and curved spacetimes for wormhole dynamics. Additionally, alternative models of traversable wormholes that do not require exotic matter are discussed. Our aim is to evaluate the plausibility of traversable primordial wormholes and to elucidate their potential significance in shaping our understanding of the universe’s earliest stages.